Peasant promotion from pastoral work - López Rivera, Luis Jesús (1984)
After ten years of pastoral work in the peasant sector of the South Andean region, knowing and living some enriching experiences and others negative, one, looking back and projecting his work for the future, reassesses the importance of having known how to go, as a Church, collecting the cry of our Andean people and having accompanied them in their continuous process of becoming aware and organizing, to enforce their rights and the rights of a region that, like the South Andean region, is marginalized and plundered by centralism . And he feels, at the same time, that this people is assuming these attitudes and commitments as a requirement of their Christian faith and their right to a more humane life.